L’attività di prevenzione primaria e il ruolo svolto dall’assistente sociale del Ser.D. - Trotta, Aurora; Donnoli, Donato (Mission - Open Access, 2023)
This paper focuses attention on one of the types of social interventions that see the commitment of the Ser.D. concerning the design and implementation aspects of primary prevention activities aimed at intervening in so-called “health promotion”.